Energy Sector Quasi-Fiscal Activities in the Countries of the Former Soviet Union - Tsyvinski, Aleh (IMF Working Papers; Working Paper ;, 2002)
A decade into the transition, many of the successor states of the former Soviet Union (FSU) continue to use energy sector quasi-fiscal activities (QFAs), especially low energy prices and the toleration of payment arrears, to provide large implicit and untargeted subsidies. These activities disguise the overall size of the government, cause overconsumption and waste, and contribute to macroeconomic imbalances. This paper analyses such activities in FSU countries, with particular emphasis on two case studies (Azerbaijan and Ukraine). The paper's policy conclusions point to the need to increase energy prices, combined with a strengthening of safety nets to protect the poor, better enforcement of payment discipline, and more efforts to achieve fiscal transparency.